Education and Training for Fish Farmers in East Sinjai District, South Sulawesi on the Use of Equipment and Monitoring of Water Quality in Ponds - Jarir, Dewi Virgiastuti; Fatwasari, Fina; Bafdah, Muh. Afif (Majalah Pengabdian Indonesia, 2025)
East Sinjai District is one of the main aquaculture centers in Sinjai Regency, South Sulawesi, with milkfish (Chanos chanos) and whiteleg shrimp (Litopenaeus vannamei) as its primary commodities. However, pond productivity remains fluctuating due to unstable water quality and the limited ability of farmers to independently monitor environmental parameters. This community service program aimed to enhance the capacity of local fish farmers through education and training on the use of water quality measuring instruments (thermometer, pH meter, and refractometer) as well as pond water quality monitoring techniques. The activity was conducted on September 12, 2025, in East Sinjai District, involving ten (10) fish farmers and lasting for four weeks. The method used was a participatory approach, covering stages of socialization, training, field practice, and mentoring. Farmers were trained to use simple measuring tools such as thermometers, pH meters, and refractometers, and were taught calibration procedures, data recording, and interpretation of measurement results. The results showed improved farmers’ skills in monitoring key water quality parameters (temperature, pH, and salinity), as evidenced by water quality monitoring conducted by five (5) participants. This program successfully enhanced farmers’ awareness, technical skills, and independence in maintaining pond environmental quality. Furthermore, it holds potential for sustainability through the formation of independent farmer groups and continued training on waste management and eco-friendly aquaculture technologies.